Detaillierte Analyse der Aufbauschneidenbildung bei der Trockenzerspanung von Stahl C45E mit Berücksichtigung des Werkzeugverschleißes - Kümmel, Johannes (Schriftenreihe des Instituts für Angewandte Materialien, Karlsruher Institut für Technologie, 2016)
In this work a new understanding of built-up edge formation was developed by applying new methods. For the first time built-up edge formation was examined in-situ in a relevant cutting parameter range by radiographic and optical methods with high temporal resolution. Additionally sophisticated analytical techniques were applied for the ex-situ examination of the microstructure in the built-up edge. A correlation between built-up edge formation and tool wear was deduced.